Preparation, Characterization And Application Of Polypyrrole-Chitosan Conducting Polymer Composite - M.Abdi, Mahnaz (2009)

(untitled)
Polypyrrole-chitosan (PPy-CHI) conducting polymer composite films were prepared by electropolymerization of pyrrole (Py) in the presence of chitosan (CHI) and ptoluenesulfonic acid sodium salt (P-TS) at room temperature. The PPy-CHI composite films were synthesized by electrochemical method on the ITO glass surface from different concentrations of pyrrole, CHI, and P-TS at different applied voltages. For comparison purposes, film formed from chitosan in acetic acid (CA) by casting method and PPy film without chitosan were prepared. The electrical conductivity measurements revealed that the composite film prepared from the solution containing 0.3 M pyrrole, 0.1 M p-TS and 0.7% (w/v) of CHI at 1.2 volt (against SCE) in 2 hrs, had the highest conductivity of 69.1 Scm-1 measured at room temperature. The electrical conductivity measurement and the DMA results showed the enhanced conductivity and mechanical properties of the prepared conducting polymer composite films were due to the presence of CHI in the composite films.